2011
DOI: 10.1080/10803548.2011.11076879
|View full text |Cite
|
Sign up to set email alerts
|

Neck–Upper Extremity Musculoskeletal Disorders Among Workers in the Telecommunications Company at Mansoura City

Abstract: Objectives. This study was to determine the prevalence and work-related risk factors of neck-upper extremity musculoskeletal disorders (MSDswork-related musculoskeletal disorders carpal tunnel syndrome video display terminal telecommunication workers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
2
8
1
1
Order By: Relevance
“…Lower back pain appeared in about 16 % of subjects, which is less than in recent research (10). However, in our study, back pain was often a cause for sick leave, which was not the case with upper back or neck pain.…”
Section: Discussioncontrasting
confidence: 85%
“…Lower back pain appeared in about 16 % of subjects, which is less than in recent research (10). However, in our study, back pain was often a cause for sick leave, which was not the case with upper back or neck pain.…”
Section: Discussioncontrasting
confidence: 85%
“…Alshagga et al (2013) found a the prevalence of musculoskeletal pain (MSP) among medical students was significantly associated with the academic year, history of trauma, family history of MSP and BMI [48]. In addition, some epidemiological studies have reported that middle-aged employees are most vulnerable to pain in neck and shoulder [49,50]. Other researches confirm working environment is not the only factor that has an impact on the development of musculoskeletal disorders individual characteristics such as gender, age, and BMI are also contributors [46,51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate logistic regression analysis showed that the oldest participants (50–70 years old) were more than 2 and 3 times as likely to have MS complaints in shoulder and elbow areas. Some epidemiological studies have reported that middle-aged employees are most vulnerable to pain in neck and shoulder localizations [ 4 , 8 , 41 43 ]. One could assume that the respondents of this particular age group have the largest experience of working with computers; however, our study did not confirm that biggest work experience associated with higher prevalence of MS pain.…”
Section: Discussionmentioning
confidence: 99%